Issue of 'An t-Óglach', Easter 1963, dedicated to Reginald Dunne and Joseph O’Sullivan, and newspaper cuttings relating to the shooting of Sir Henry Wilson and Rex Taylor's book 'Assassination' - O'Shannon, Cathal, 1889-1969; O'Sullivan, Patrick, Vice Commandant, London IRA; Lee, Frank K.; McManus, Francis Patrick Vincent, 1905- (1922)
Includes reviews and articles by Cathal O'Shannon, Frank Lee and Patrick O'Sullivan.
Keywords: Dunne, Reginald, -- -1922; O'Sullivan, Joseph, -- 1897-1922; Wilson, Henry Hughes, -- Sir, -- 1864-1922.; Taylor, Rex, -- 1921-; Ireland -- History -- 1922-